PENERAPAN STRATEGI PEMBELAJARAN PENINGKATAN KEMAMPUAN BERPIKIR (SPPKB) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 163 KOTA PEKANBARU - Gayanti, Febbri; ', Erlisnawati; ', Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrck The problems in the research is learned social science still low, There are many students can’t understanding basic concepts and tend to memorize an example. It can be seen from the percentage of the value examps. Students who reached (criteria minimum value ) In fourth class of public elementary school 163 city pekanbaru is 43,59 % From 39 students the average value is 64,79. And the KKM set school is 70. Of the problems the act of class research needs to be done by applying a model strategy of learning increase the capacity to think (SPPKB). This research aimed to find out if the application of a model learning strategy of learning increase the capacity to think (SPPKB) it could improve study result the social science In fourth grade of public elementary school 163 city pekanbaru The academic year 2014 / 2015 as the number of students 39. This research done in the three cycles, the first Cycle consists of three times a meeting with a daily examps. The cycle of second and third also consist of three times a metting with daily examps. the data on this research by using the observation activity sheet teacher, and using the observation activity sheet student dan with daily examps.and be applying a model strategy of learning increase the capacity to think (SPPKB) can be increase study result of social science student and percentage of complete on base score is 43,59% become 46,15% in the first cyle, in the second cycle become 74,36% and in the third cycle become 93,30%. An instrument collecting data using sheets of observation teachers and the activity of a student during the learning process In fourth class A of public elementary school 126 pekanbaru. The percentage activity of teacher in the first cycle is 59,37%, second cycle become 74,95% and third cycle become 92,19%, and the percentage of activity student in the first cycle is 60,41%, second cycle become 74,99% and the third cycle become 91,66%. The based on the result can be concluded the applying a model strategy of learning increase the capacity to think (SPPKB) in the social science in the fourth class public elementary school 163 city pekanbaru can be received.Key Word : The Application Of Learning Strategy Increasing The Capacity To Think To Increase Study Result Of The Social Science2